Digital Trust and Consumer Loyalty in AI-based E-commerce: An Analysis of Indonesian Millennials - Dwi Febri Syawaludin; Muhammad Nasir (Politeknik Siber Cerdika Internasional, 2025)
Advances in artificial intelligence (AI) technology have significantly changed the e-commerce landscape, influencing consumer behavior and loyalty. This study aims to analyze the influence of digital trust on consumer loyalty among Indonesian millennials in the context of AI-driven e-commerce. This research uses a qualitative approach with in-depth interviews and digital ethnography, involving Indonesian millennials who actively shop on AI-based platforms. The main findings of this study show that trust in digital platforms, especially those related to data security, algorithm transparency and privacy protection, strongly influence consumer loyalty. Furthermore, AI-based personalization can increase trust, but only if transparency in algorithmic data usage is clearly provided. The study also found that AI competence plays an important role in strengthening the relationship between trust and consumer loyalty. The implications of this study point to the importance of implementing clear transparency policies and ethical data management in building trust and increasing loyalty, especially in emerging markets such as Indonesia. The findings can help e-commerce companies design more effective AI strategies, improve user experience and mitigate privacy concerns.